Depiction of Ishana holding a Trishula - Temples of India Project Team (Jio Institute, 2024)
At the opposite side of Kubera, Ishana is depicted, holding a trishula (trident) in his upper right hand, albeit now damaged. His upper left-hand grasps a sarpa (serpant), while his lower left-hand holds a kamandalu (water pot). Positioned in Varada hasta (hand gesture of conferring a boon), his lower right-hand carries a rosary. At the bottom, a bull was originally carved, though it's now broken.